A laboratory for industrial research on mass customisation in the footwear industry. (24th July 2006) - Redaelli, Claudia; Sorlini, Marzio; Boer, Claudio R.
This case study describes and analyses an Italian-based laboratory as a state-of-the-art approach to the mass customisation of shoe design and manufacturing. Based in Italy's shoemaking capital, Vigevano, the ITIA-CNR Design & Mass Customisation Laboratory (D&MC Lab) covers the entire spectrum of development and production activities of mass-customised shoes: based on a digital foot scan and an evaluation of customers' wishes, customised shoes are manufactured. The case study covers internal changes required during production, information processing and human resources management, and comments on the need to consistently manage the relationships with other external actors of the value chain for successful mass customisation.